Optimization of Customer Complaint Resolution Through a Digitally Traceable Process Framework and Value Stream Mapping in The Automotive Industry - Nashiruddin, Muhammad; Sundari, Susanti; Purba, Humiras Hardi (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Improving customer complaint handling is crucial for the sustainability and success of a business, as efficient and responsive complaint handling demonstrates a company's commitment to meeting customer needs and expectations, thereby enhancing customer satisfaction. The automotive industry sets a 14-day working day standard for complaint resolution. However, the actual complaint handling process often takes an average of 26 days. By implementing a traceability system, integrating a Value Stream Mapping (VSM) approach, and adopting Industry 4.0 transformations, this research aims to reduce the handling time. Moreover, by mapping the workflow through Visual Stream Mapping, inefficiencies can be identified, and through the implementation of a Traceability System and the development of system-based processes, the transformation achieved through the conceptual model of Industry 4.0 adoption can improve the process from 26 working days to 7 working days. Keywords: Customer Complaint, Traceability, VSM